Pengaruh Komitmen Manajemen Kapal Allianz Middle East Terhadap Pelayanan Jasa Transportasi dan Jaminan Keselamatan Penumpang serta Crew - Tarakka, Neiten; Asmoro, Eddi Indro; Oktoberty, Oktoberty (Universitas Ivet, 2024)
The Indonesian Sea is very important for the Republic of Indonesia, namely the sea as a medium for unifying the nation, the sea as a medium of communication, the sea as a resource medium, the sea as a medium of defense and security, and the sea as a medium of diplomacy. Freight or sea transportation in Indonesia has an important role in advancing and expediting domestic and foreign trade. Allianz Middle East's obligations or responsibilities as a transportation company and the passenger's right to enjoy these facilities cannot be separated from the element of passenger safety which is the main priority. The research aims to determine Allianz Middle East transportation services on offshore service vessels. To find out the safety of passengers and crew on the Pioneer ship at Allianz Middle East LLC. The test results show a positive and significant influence between service on the management commitment of the Allianz Middle East ship, and other tests show a positive and significant influence between the safety assurance variable and the management commitment variable.